Novel Drug Development for Anti-Cholesterol Activity by in silico Analysis: Identification Cholesterol Inhibiting Compounds - Kura, Ananya M; KarukuvelRaja, R; Pillai, Thulasi G (Asian Journal of Biological and Life Sciences)
Aim: Cholesterol is required for cellular metabolism and steroid hormone production. However, the excessive level leads to the condition known as hypercholesterolemia, which causes cardiovascular illnesses. A number of drugs can lower blood cholesterol levels, but these medications have a variety of negative effects. The microalgae possess wide range of bioactive compounds, which would be used to treat the abnormal cholesterol levels. Materials and Methods: This study aims to determine the anticholesterol activity of bioactive compounds of the selected microalgal species (Chlorella, Anabaena, Oscillatoria, and Lyngbya) via in silico study. Druglikeness analysis were carried out for the 226 compounds, based upon the results 81 compounds were selected for molecular docking. Results: The ADMET analysis and PASS prediction was performed for the 5 best docked compounds such as Debromoaplysiatoxin, Spiroidesin, Oscillatoxin A, Ergosta-8,(9)14-dien-3beta-ol, and Cyclindrospermopsin. Conclusion: Hence, these compounds can be used to develop the novel cholesterol lowering drugs.
Keywords: Anabaena; Chlorella; cholesterol; Lyngbya; Molecular docking; Oscillatoria